A Christian Habitus: Wittgenstein and Liturgical Formation - Kopack, Austin C. (Lumen et Vita, 2019)
What is the relationship between preaching and living the Gospel? It is within the daily habits of those attempting to live out the Gospel together that preaching becomes intelligible and applicable. Sound preaching alone will fail to produce a transformed people whose lives reflect the teachings of scripture. This paper brings together the linguistic philosophy of Ludwig Wittgenstein and the theological anthropology of James K. A. Smith in order to develop an affective pedagogy that takes seriously the socially dependent nature of human persons. The social account of language proposed in the later Wittgenstein suggests that the meaning of concepts arises amongst pre-linguistic, embodied, communal practices. Theological language cannot be detached from its concrete expressions in the world because its meaning is dependent upon a communal form of life in which those concepts make sense. James K. A. Smith builds upon this pragmatist tradition to present a theory of doctrine and preaching grounded in liturgical practices that does justice to human physicality and characterizes all human practices, religious or otherwise, as structures of habitual formation with particular teloi. The Gospel, then, is not just a truth we learn to believe but a way of life that we come to embody contra competing “cultural liturgies.”